Of thee i sing ebook A letter to my daughters. - Obama, Barack (2010)
Barack Obama delivers a tender, beautiful letter to his daughters in this powerful picture book illustrated by award-winner Loren Long that's made to be treasured! In this poignant letter to his daughters, Barack Obama has written a moving tribute to thirteen groundbreaking Americans and the ideals that have shaped our nation. From the artistry of Georgia O'Keeffe, to the courage of Jackie Robinson, to the patriotism of George Washington, Obama sees the traits of these heroes within his own children, and within all of America’s children.   Breathtaking, evocative illustrations by award-winning artist Loren Long at once capture the personalities and achievements of these great Americans and the innocence and promise of childhood.   This beautiful book celebrates the characteristics that unite all Americans, from our nation’s founders to generations to come. It is about the potential within each of us to pursue our dreams and forge our own paths. It is a treasure to cherish with your family forever.